2018
DOI: 10.15587/2519-4852.2018.153199
|View full text |Cite
|
Sign up to set email alerts
|

Search of the promising species of subfamily Amygdaloideae and Pyroideae using the chemotaxonomy

Abstract: Світова флора нараховує понад 1000 видів роду Сrataegus L., до підроду Prunus L. належать понад 30 видів, рід Malus Mill. містить 100 видів, до підріду Cerasus Juss. відноситься понад 150 видів. Незважаючи на різноманіття видів та достатню сировинну базу, лише деяки представники цих родів достатньо досліджені та знайшли своє використання як джерела біологічно активних речовин (БАР). Мета. Провести хемотаксономічне дослідження представників родів Сrataegus L., Prunus L., Malus Mill., Cerasus Juss.; встановити п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…As we reported earlier, when conducting chemo-taxonomic and morphological-taxonomic studies of leaves, fruits and flowers of non-pharmacopoeial representatives of the hawthorn genus, promising species for the further in-depth study were identified [9]. When studying the chemical composition of the leaves of representatives of the section Molles Sarg.…”
Section: Introductionmentioning
confidence: 89%
“…As we reported earlier, when conducting chemo-taxonomic and morphological-taxonomic studies of leaves, fruits and flowers of non-pharmacopoeial representatives of the hawthorn genus, promising species for the further in-depth study were identified [9]. When studying the chemical composition of the leaves of representatives of the section Molles Sarg.…”
Section: Introductionmentioning
confidence: 89%